Dominant Trees in a Subtropical Forest Respond to Drought Mainly via Adjusting Tissue Soluble Sugar and Proline Content - Kuang, Yuanwen; Xu, Yimin; Zhang, Lingling; Hou, Enqing; Shen, Weijun (Frontiers in Plant Science, 2017)
It is well-known that drought has considerable effects on plant traits from leaf to ecosystem scales; however, little is known about the relative contributions of various traits within or between tree species in determining the plant’s sensitivity or the tolerance to drought under field conditions. We conducted a field throughfall exclusion experiment to simulate short-term drought (~67% throughfall exclusion during the dry season from October to March) and prolonged drought (~67% throughfall exclusion prolonging the dry season from October to May) and to understand the effects of drought on two dominant tree species (Michelia macclurei and Schima superba) in subtropical forests of southern China. The morphological, physiological, and nutritional responses of the two species to the two types of drought were determined. There were significantly different morphological (leaf max length, max width, leaf mass per area), physiological (leaf proline) and nutritional (P, S, N, K, Ca, Mg) responses by M. macclurei and S. superba to prolonged drought. Comparison between the drought treatments for each species indicated that the trees responded species–specifically to the short-term and prolonged drought, with S. superba exhibiting larger plasticity and higher adaption than M. macclurei. M. macclurei responded more sensitively to prolonged drought in terms of morphology, proline content, and nutritional traits and to short-term drought with regard to soluble sugars content. The differential species-specific responses to drought will allow us to estimate the changes in dominant trees in subtropical forests of China that have experienced a decade’s worth of annual seasonal drought.